Various Ischemic Events Following Facial Autologous Fat Injection: A Case Report - Arash Tabaraee; Mahdi Rezai; Hasan Amiri; Taha Mohammad Ahmadivash; Seyedamir Tabibzadeh dezfooli (Case Reports in Clinical Practice, 2023)
Facial rejuvenation and augmentation with autologous fat injection are common and effective techniques worldwide. This procedure has few complications and is usually used for soft-tissue augmentation. Although this procedure is considered safe, many patients have experienced different complications such as visual loss, stroke, or skin necrosis after these procedures. Herein, a case of embolic stroke along with blindness and facial necrosis due to facial filler injection is described. In this case, a patient developed decreased level of consciousness, left hemiparesis, and blindness that was finally diagnosed based on imaging as embolic stroke following facial autologous fat injection. The symptoms improved partially and gradually by conservative treatment and the patient was discharged with some sequels.